DEVELOPMENT OF AN AUGMENTED REALITY-BASED POCKET BOOK USING THE DISCOVERY LEARNING MODEL TO INCREASE STUDENT INTEREST AND LEARNING OUTCOMES IN CLASS X HIGH SCHOOL VIRUS MATERIAL - Ditasari, Kania; Suwondo, Suwondo (Bio-Lectura : Jurnal Pendidikan Biologi, 2024)
This research aims to design pocket book teaching media so that students are enthusiastic in the learning process. Students find it difficult to understand virus material because they cannot see it directly, so it is designed using augmented reality using a discovery learning model in the design of a learning pocket book which was developed to increase student interest and learning outcomes. The development process was carried out using ADDIE, namely analysis, design, development, implementation and evaluation in the FKIP UNRI Masters Program, the second stage of experimentation at SMAN 1 Tembilahan. The analysis stage was carried out by observation using a questionnaire and the design stage was carried out using various computer software. The result of this research is a pocket book design based on augmented reality. Learning by displaying abstract biological objects in 3D and animation through the use of technology is expected to make students better understand the material obtained, one of which is augmented reality. Based on the results of development and implementation testing of the product, it was found that the product quality was very good and the increase in interest and learning outcomes in the experimental class increased significantly compared to the control class. It is hoped that the results of this research can be developed and carried out further.